SPECIFIC TECHNIQUES FOR THE EXAMINATION OF ART AND ANTIQUES FOR THE PURPOSES OF FORENSIC COMMODITY EVALUATION - A. Selivanov (Теория и практика судебной экспертизы, 2015)
The capabilities of forensic commodity evaluation of art objects and antiques are illustrated with casework examples.